Current Options for Measuring the Surface Temperature of Dairy Cattle in a Stable Technology: Review - Kateřina Švejdová; Miloslav Šoch; Anna Šimková; Anna Švarcová; Tomáš Frejlac; Luboš Zábranský; Bohuslav Čermák (Scientific Papers Animal Science and Biotechnologies, 2023)
Regular measurement of the body surface temperature can help to assess the health status of animals. There are many technological possibilities of contactless temperature measurement of body surface. The important thing is to find the right part of the body whose temperature will point to the first possible symptoms and immediately react to the first signs of the disease. Disagreements about how to measure body surface temperature and accuracy of the method can occur when different measures are used. We review work showing possibilities of contactless surface temperature measurements using 1) thermography, 2) electronic transponders and 3) other possibilities of measuring the body surface temperature of dairy cattle. For example, when we scan the surface temperature with the thermal imager there can operate in individual animals confounding factors such as the nature or degree of muscular coat, which may significantly affect the results.